Climate policy with the chequebook: Economic considerations on climate investment support - Karol Kempa; Ulf Moslener (Frankfurt School of Finance & Management, 2015)
Across the globe climate policy is shifting away from a carbon price towards investment subsidies, such as grants, interest-subsidised loans or guarantees. This increases the risk of inefficient public spending. This paper shows how the main market imperfections related to the emission externality, knowledge spillovers and capital market imperfections negatively affect the risk-return-profile of a climate investment. To some extent these negative impacts can be compensated through different forms of investment subsidies. Minimising the risk of inefficient public spending is, however, challenging and requires detailed understanding of technologies and markets at the project level. The analysis provides guidance for the design of appropriate investment subsidy schemes. Carbon prices and investment subsidies are not perfect substitutes, and - at least for developed economies - a carbon price remains the single most efficient instrument. This price should, however, coexist with other instruments, e.g. investment support schemes, which can be tailored to address the non-emission market imperfections related to climate change.
Keywords: 330; climate finance; investment support; policy instruments; environmental externality; innovation spillover; capital market failure